KORELASI ANTARA RESIDU INSEKTISIDA BERBAHAN AKTIF KLORPIRIFOS DENGAN KARAKTERISTIK FISIK KACANG PANJANG (Vigna sinensis) YANG DIJUAL DI PASAR TRADISIONAL KOTA DENPASAR - Wawan Wijaya, I Made; Lani Triani, I Gst. Ayu; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
This study aims to 1) calculating residual insecticide chlorpyrifos active substance in long beans, 2) determine the physical characteristics of the beans, and 3) calculating the correlation between residual insecticide chlorpyrifos active substance and physical characteristics long beans that was sold in Denpasar traditional market. Based on purposive sampling method, 43 long beans seller obtained from 9 subdistrict. Insecticide residues correlated with some physical characteristics of the product moment correlation by using a computer program package Statistical Product and Servise Solution 17.0 for Windows. The result of this research showed average residual insecticide chlorpyrifos active substance in long beans from Banyuwangi Subdistrict with 0.0025 mg/Kg, Kabat Subdistrict with 0.0022 mg/Kg, Singojurun Subdistrict with 0.0015 mg/Kg, Srono Subdistrict with 0.0009 mg/Kg, Baturiti with 0.0035 mg/Kg, Kerambitan Subdistrict with 0.0011 mg/Kg, Marga Subdistrict with 0.0023 mg/Kg, Penebel Subdistrict with 0.0040 mg/Kg, and Tabanan Subdistrict with 0.0010 mg/Kg. The resulted of sensory evaluation by the color criteria from lime green to dark green, from hard to soft texture, and the percentage of damage from 0-20% to 41-60%. The correlation between residual insecticide with colors have a real significance level with a value of correlation coefficient 0.702, the correlation between the texture residual insecticides and insecticide residues correlation between the percentage of damaged have unreal significance level with the correlation coefficient value 0.565 and 0.398 respectively
Keywords: 30